Remote Patient Monitoring System For Covid-19 Patient Using Wi-Fi-Based Pulse Oximeter Reading Sensor - Muhammad Akmal Mohd Takiyuddin; Iman Hazwam Abd Halim; Tajul Rosli Razak; Mohd Faris Mohd Fuzi (Journal of Computing Research and Innovation, 2022)
Continuous Heart disease and blood pressure are diseases that demand immediate care. Heart disease is currently one of the world's most fatal illnesses, as it always results in death. Pulse Oximeter Reading must be continuously measured, analyzed, and monitored in real-time to ensure that relevant measures may be taken when necessary. In this paper, we present a model that employs IoT to inform users about the incidence of heart disease and high blood pressure in their daily health. The Remote Patient Monitoring System for Covid-19 Patients Based on Oximeter Reading Sensor uses the Web Server ESP32 MAX30100 to replace the present Oximeter Reading monitoring and public broadcasting approaches. In addition, the NodeMCU ESP8266 Wi-Fi module allows the devices to save data in the cloud when connected to the Internet. Also, it is possible to construct effective real-time Heart Rate and Oxygen Level (IoT) monitoring. The findings indicated that users might access and monitor Heart rate and oxygen level via the Web Server regardless of their location in the monitoring region. Furthermore, providing an LCD is incredibly beneficial as it can show readings and ensure the users receive Pulse Oximeter Reading monitoring information when the device is in operation.